Методологічні аспекти вивчення та оптимізації дендроценозу Тростянецького парку - Ilyenko, А.А.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
It was given the description of dendrocenosis of Trostyanets park by the way of conceptual model provided with quantitative examinations of dynamics of number and age structure under populations level within general scheme of systems approach to study of natural ecosystems. The methodological approaches of study of the park ecosystem and development of basic positions of the optimization program of Trostyanets park were determined.